New directions in climate justice? A dialogue between critical climate justice and policy studies scholars - Andrea Schapper; Paul Cairney; Neil Crawford; Clemens Hoffmann; Hyeyoon Park; Hannes Stephan (Earth System Governance)
New directions in just climate policymaking can emerge from the dialogue between critical climate justice and policy studies scholars. Current climate justice research presents a strong and coherent message about the scale and urgency of climatic challenges, historical responsibilities, colonialism, systemic inequalities, intersectionality and the role of recognitional, procedural, and distributional justice-driven solutions. However, it struggles to explain how to overcome profound gaps between aspiration and reality. In this Perspective, we bring insights from critical climate justice scholars and policy scholars into conversation. Policy theories help us explain gaps between high ambitions but low progress towards policymaking integration and policy coherence for climate justice. However, they focus largely on evidence from Western countries and struggle to harness wider international insights on policy innovation, with the potential to largely contribute to a doom spiral. We use the example of non-anthropocentric policymaking and planetary justice approaches to explore this dialogue on drivers and barriers to change.